A Comprehensive Literature Review of Perinatal Diagnosis, Management, and Follow-up of Cystic Renal Diseases - Samuel, Samuel; Livia, Livia (The Indonesian Journal of General Medicine, 2024)
Background: The literature on perinatal diagnosis, management, and follow-up of cystic renal diseases reflects a significant evolution in clinical practices, driven by advancements in imaging technology and a deeper understanding of renal anomalies. The studies reviewed highlight the critical role of prenatal ultrasonography in identifying urinary tract anomalies, which account for a notable percentage of congenital conditions. Literature Review: Together, these studies illustrate a comprehensive landscape of research surrounding cystic renal diseases, emphasizing the critical interplay between prenatal diagnosis, management strategies, and postnatal outcomes. The evolving understanding of these conditions underscores the importance of continued research and refinement of clinical practices to enhance prognostic counseling and improve patient care. Conclusion: The collective insights from these studies underscore the importance of early detection and tailored management strategies in improving outcomes for affected infants. The integration of advanced imaging techniques and a multidisciplinary approach is essential for enhancing prognostic counseling and guiding clinical decision-making. Continued research is necessary to refine these practices and address the complexities associated with cystic renal diseases.